Investigation of the kinetic laws affecting the organic suspension granulation in the fluidized bed - Ostroha, Ruslan; Yukhymenko, Mykola; Yakushko, Serhiy; Artyukhov, Artem (Eastern-European Journal of Enterprise Technologies, 2017)
The authors prove that it is possible to reduce economic and environmental parameters in the processes of granulation and produce fertilizers by recycling, and further reprocessing of chicken manure. This prevents unprocessed manure from getting into the environment, and due to the organic origin of the material, the soil is not contaminated. In order to reduce the cost of processing wet substances and increase homogeneity of the final product granulometric composition, it is proposed to fulfill granulation of organic suspensions in the fluidized bed devices. The mechanism of granule formation in a fluidized bed was studied and granulation temperature modes of organic suspensions were experimentally established. The process operating parameters have been determined, namely, maintaining temperature in the fluidized bed at 70 °C, one can continuously produce organic granules of high density and strength. Heat transfer kinetics of organic suspension dehydration was studied, as well as convective heat transfer in the suspended layer was determined. Based on the obtained experimental data, the coefficient of heat transfer from the heat agent (air) to the surface of solid particles during evaporation of the suspension was calculated. The obtained criteria dependence makes it possible to predict a value of the heat transfer coefficient for the granulation process of chicken manure suspension. The technological scheme of the production line for granular organic fertilizers for the cultivation of ecologically pure food products, which also takes into account the specific properties of unprocessed chicken manure, is proposed.